EVALUATION OF KM-4 CONCRETE PAVEMENT THICKNESS, LEMO VILLAGE ACROSS NORTH BARITO REGENCY - Sonia Fatimah; Yasruddin Yasruddin; Nova Widayanti (Universitas Lambung Mangkurat, 2023)
Roads are transportation infrastructure used by the Indonesian people to carry out daily mobilization activities so that the volume of vehicles that pass through these roads affects their capacity and carrying capacity. Along with developments in North Barito Regency, one of which is the road in Lemo Village, it has become an alternative road to the road section of the capital city of Central Kalimantan Province, Palangka Raya.Planning for widening the Lemo Village road has the aim of determining the thickness of the rigid pavement which is guided by the Road Pavement Design Manual Number 02/M/BM/2017 and controlled using the Cement Concrete Road Pavement Planning guideline Pd T-14-2003 and then calculates the Budget Plan. on the widening of the Km 4 concrete pavement of Lemo Seberang Village.In planning the thickness of rigid pavement structures using the Road Pavement Design Manual Number 02/M/BM/2017, the concrete slab = 26.5 cm; LMC foundation layer = 10 cm; Drainage layer = 15 cm and using Cement Concrete Pavement Planning Guidelines Pd T-142003 obtained concrete slab = 25 cm; foundation layer = 10 cm. In addition, for data on field conditions in the form of a concrete slab = 25 cm; layer of concrete K-125 = 10 cm, then the efficient pavement thickness is taken, namely the Cement Concrete Pavement Planning Guidelines Pd T-14-2003 which is more efficient than field conditions. And also in writing this final project, it also discusses the Budget Plan for the widening of the KM 4 concrete pavement, Lemo Seberang Village, North Barito Regency. Keywords: Road Pavement Design Manual Number 02/M/BM/2017, Guidelines for Planning Cement Concrete Road Pavement Pd T-14-2003, Budget Plan